Gender, Sexuality, and Colonial Modernities, and: The Erotic Margin: Sexuality and Spatiality in Alteritist Discourse (review) - Carter, Julian B.; Klotz, Marcia (Journal of the History of Sexuality, 2001)
Reviews two books on postcolonial studies on modernity. "Gender, Sexuality, and Colonial Modernities," by Antoinette Burton; "The Erotic Margin: Sexuality and Spatiality in Alteritist Discount," by Irwin Scilick.
Keywords: amériques; approches et analyses; canada; europe; féminisme décolonial; genre; identités LGBTQIA2+; intersectionnalité; ressource en ligne; régions géographiques; sexualité; thématiques; études de genres